Treatment Strategy of a Recurrent Squamous Cell Pancreatic Carcinoma with Peritoneal Carcinomatosis - Tentes, A.; Fotiadou, A.; Kyziridis, D.; Hristakis, Ch.; Kalakonas, A.; Iliadis, A. (New Visions in Medicine and Medical Science Vol. 7, 2024)
Background: Pancreatic squamous cell carcinoma is an uncommon condition, and little is known about its pathogenesis. The only possible curable procedure is surgical resection. Palliative care is typically administered for recurrent local-regionally located pancreatic carcinomas, as they are typically incurable. Aim: The purpose of the study is to present the treatment strategy of a recurrent squamous cell pancreatic carcinoma with peritoneal carcinomatosis. Case Report: A 49-year-old man with local-regional recurrent squamous cell pancreatic carcinoma underwent complete (CC-0) cytoreductive surgery (CRS) and hyperthermic intraoperative intraperitoneal chemotherapy (HIPEC). In a 6-month time he underwent secondary CRS+HIPEC for regional recurrence. Despite treatment with adjuvant systemic chemotherapy the patient died 12 months after the initial CRS with osseous metastases. The biologic behavior and the clinical presentation do not differ from ductal adenocarcinoma of the pancreas, although upper gastrointestinal tract bleeding secondary to gastric invasion appears to be more frequent in squamous cell pancreatic carcinomas. Conclusions: A reliable prognosis for recurrent squamous cell pancreatic carcinoma is difficult despite complete cytoreduction in combination with HIPEC and systemic chemotherapy. The patient presented recurrence despite aggressive treatment shortly after surgery. Although complete cytoreduction was possible very shortly the patient presented distant metastatic disease and died.